Rouxiella badensis, a new bacterial pathogen of onion causing bulb rot - Zhao, Mei; Tyson, Chris; Gitaitis, Ron; Kvitko, Brian; Dutta, Bhabesh (Frontiers in Microbiology, 2022)
Onion bulb rot can be caused by multiple plant pathogens including bacterial pathogens. During our routine survey of commercial onion farms in 2014, 2020, and 2021, seven putative Rouxiella spp. strains were isolated from symptomatic onion samples in Georgia, United States. Upon fulfilling Koch’s postulates on onion, a genome analysis was conducted. Whole-genome indices (ANI and dDDH) showed that the strains belonged to Rouxiella badensis. Although the seven R. badensis strains were not pathogenic on onion foliage, the strains were able to cause bulb rot and could also produce necrotic lesions in a red onion scale assay. Rouxiella badensis populations increased significantly and to a level comparable to P. ananatis PNA 97-1R in a red onion scale infection assay. The core-genome analysis grouped all onion R. badensis strains from Georgia together, and distinct from R. badensis strains isolated from other sources and locations. Based on the genome analysis of strains (from the current study and available genomes in the repository), type I, III (Ssa-Esc and Inv-Mxi-Spa types), and V secretion systems are present in R. badensis genomes, while type II, IV, and VI secretion systems are absent. However, various secondary metabolite gene clusters were identified from R. badensis genomes, and a thiol/redox-associated enzyme gene cluster similar to the Pantoea alt cluster mediating thiosulfinate tolerance was also present in onion strains of R. badensis. This is the first report of R. badensis as a plant pathogen.